The UK stand together trial: protocol for a multicentre cluster randomised controlled trial to evaluate the effectiveness and cost-effectiveness of KiVa to reduce bullying in primary schools - Suzy Clarkson; Lucy Bowes; Elinor Coulman; Matthew R. Broome; Rebecca Cannings-John; Joanna M. Charles; Rhiannon Tudor Edwards; Tamsin Ford; Richard P. Hastings; Rachel Hayes; Paul Patterson; Jeremy Segrott; et al. (BMC, 2022)
Abstract Background Reducing bullying is a public health priority. KiVa, a school-based anti-bullying programme, is effective in reducing bullying in Finland and requires rigorous testing in other countries, including the UK. This trial aims to test the effectiveness and cost-effectiveness of KiVa in reducing child reported bullying in UK schools compared to usual practice. The trial is currently on-going. Recruitment commenced in October 2019, however due to COVID-19 pandemic and resulting school closures was re-started in October 2020. Methods Design: Two-arm pragmatic multicentre cluster randomised controlled trial with an embedded process and cost-effectiveness evaluation. Participants: 116 primary schools from four areas; North Wales, West Midlands, South East and South West England. Outcomes will be assessed at student level (ages 7-11 years; n = approximately 13,000 students). Intervention: KiVa is a whole school programme with universal actions that places a strong emphasis on changing bystander behaviour alongside indicated actions that provide consistent strategies for dealing with incidents of bullying. KiVa will be implemented over one academic year. Comparator: Usual practice. Primary outcome: Student-level bullying-victimisation assessed through self-report using the extensively used and validated Olweus Bully/Victim questionnaire at baseline and 12-month follow-up. Secondary outcomes: student-level bullying-perpetration; student mental health and emotional well-being; student level of, and roles in, bullying; school related well-being; school attendance and academic attainment; and teachers' self-efficacy in dealing with bullying, mental well-being, and burnout. Sample size: 116 schools (58 per arm) with an assumed ICC of 0.02 will provide 90% power to identify a relative reduction of 22% with a 5% significance level. Randomisation: recruited schools will be randomised on 1:1 basis stratified by Key-Stage 2 size and free school meal status. Process evaluation: assess implementation fidelity, identify influences on KiVa implementation, and examine intervention mechanisms. Economic evaluation: Self-reported victimisation, Child Health Utility 9D, Client Service Receipt Inventory, frequency of services used, and intervention costs. The health economic analysis will be conducted from a schools and societal perspective. Discussion This two-arm pragmatic multicentre cluster randomised controlled trial will evaluate the KiVa anti-bullying intervention to generate evidence of the effectiveness, cost-effectiveness and scalability of the programme in the UK. Our integrated process evaluation will assess implementation fidelity, identify influences on KiVa implementation across England and Wales and examine intervention mechanisms. The integrated health economic analysis will be conducted from a schools and societal perspective. Our trial will also provide evidence regarding the programme impact on inequalities by testing whether KiVa is effective across the socio-economic gradient. Trial registration Trials ISRCTN 12300853 Date assigned 11/02/2020.